Even Cowboys Carry Cell Phones - Milbrodt, Teresa, 1978- (Book collections on Project MUSE., 2013)
Like any legendary figure, the cowboy is part myth and part reality, memorialized by history and Hollywood, envied by those who spend days at desks and dream of trading swivel chairs for saddles. The writings in this anthology serve as testament to the cultural love, bordering on obsession, of the American cowboy. These works cover the gamut, from the romanticized movie cowboy to ranchers, freelancers, and contemporary wranglers who wear hoodies and work in massive feedlot pens.